World Development Report 1984 - World Bank (New York: Oxford University Press, 2012)
Long-term needs and sustained effort are underlying themes in this year's report. As with most of its predecessors, it is divided into two parts. The first looks at economic performance, past and prospective. The second part is this year devoted to population - the causes and consequences of rapid population growth, its link to development, why it has slowed down in some developing countries. The two parts mirror each other: economic policy and performance in the next decade will matter for population growth in the developing countries for several decades beyond. Population policy and change in the rest of this century will set the terms for the whole of development strategy in the next. In both cases, policy changes will not yield immediate benefits, but delay will reduce the room for maneuver that policy makers will have in years to come.